1999
DOI: 10.1016/s0014-5793(99)00863-7
|View full text |Cite
|
Sign up to set email alerts
|

Shortened microsatellite d(CA)21 sequence down‐regulates promoter activity of matrix metalloproteinase 9 gene

Abstract: One characteristic elements in the promoter of the matrix metalloproteinase 9 (MMP-9) gene is the d(CA) repeat. To investigate whether this element regulates the transcription of the MMP-9 gene and its enzymatic activities, we sequenced the promoter region isolated from esophageal carcinoma cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
140
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 35 publications
4
140
2
1
Order By: Relevance
“…Longer (GT)n repeats in the promoter of heme oxygenase-1 gene were associated with lower promoter activity. 37 In contrast, Shimajiri et al 48 showed that longer (CA)n repeats in the matrix metalloproteinase 9 promoter enhanced activity. We have found that shorter (np16) GT repeats in intron II of the human TLR2 gene were significantly associated with the presence of TB in this Korean population.…”
Section: Discussionmentioning
confidence: 95%
“…Longer (GT)n repeats in the promoter of heme oxygenase-1 gene were associated with lower promoter activity. 37 In contrast, Shimajiri et al 48 showed that longer (CA)n repeats in the matrix metalloproteinase 9 promoter enhanced activity. We have found that shorter (np16) GT repeats in intron II of the human TLR2 gene were significantly associated with the presence of TB in this Korean population.…”
Section: Discussionmentioning
confidence: 95%
“…Polymorphic dinucleotide microsatellites in or near promoters have been identified and found to regulate many other genes (Borrmann et al, 2003;Gebhardt et al, 1999;Shimajiri et al, 1999;Wang et al, 2005). One of the microsatellites that consists of GA repeats is highly conserved from mouse to human and is therefore likely to have human relevance.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] The number of tandem repeats has been shown to influence the transcription rate either by a direct interaction with a transcription factor 44,45 or by affecting spacing between flanking regions. 46 Considering the data of the present paper it is tempting to speculate that a long IL10.G allele might be responsible for a high IL10 production, a typical aspect of SLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%